The reference nurse in the care of children undergoing liver transplantation: A qualitative study - Ernestina Maria Batoca Silva (2022)
Introduction: The reference nurse model is based on a methodology of organization of comprehensive, individualized and continuous care, centered on the child and the family, and has its similarity with the role of family nurses in primary health care. Its theoretical conception resides in family-centered care and in the care partnership model. Goals: To describe the parents' perception of the role of the reference nurse in hospitalization and care for children submitted to liver transplantation. Methods: Qualitative, exploratory-descriptive study of a phenomenological nature, Level I, with deductive approach, through the application of semi-structured interviews to a non-probabilistic sample of 5 parents, and content analysis was performed. Results: Parents recognize the existence of a reference nurse in care during the hospitalization of their child and highlight technical/scientific and relational competencies in the performance of care, highlighting the experience, involvement with the child and family, knowledge about the child, ability to deal with the child, empathy, support and active listening. They reveal positive experiences with the care provided by the reference nurse and the entire team, showing themselves to be satisfied with the follow-up and presence by the reference nurse. Negative experiences are related to the confrontation with the disease and treatment. As proposals for improvement parents suggest greater humanization, optimize the integration of parents into the unit and care, and creation of networks and support groups. Conclusions: We believe that this study can provide contributions to optimize the use of the reference nurse model in specialized nursing care practice, with repercussions on improving the quality of care and greater parental satisfaction. The qualitative methodology allowed a more in-depth approach, allowing parents to obtain information and understanding of their way of thinking and experiences.